2011
DOI: 10.1021/ol200456y
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Magnesium BINOL Phosphate-Catalyzed Phosphination of Imines: Access to Enantioenriched α-Amino Phosphine Oxides

Abstract: A new method to synthesize chiral α-amino phosphine oxides is reported. The reaction combines N-substituted imines and diphenylphosphine oxide, and is catalyzed by a chiral magnesium phosphate salt. A wide variety of aliphatic and aromatic aldimines substituted by electron neutral benzhydryl or dibenzocycloheptene groups were excellent substrates for the addition reaction. The dibenzocycloheptene protected imines afforded improved enantioselectivity in the resulting products. Substituted diphenylphosphine oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(36 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…For example, Antilla et al have reported a novel methodology to add diphenylphosphine oxide 166a to imines with generally moderate to quantitative yields (65-98%) and enantioselectivities of up to 99% ee. 90 The process was catalyzed with only 5 mol% of chiral phosphate magnesium complex 190 in acetonitrile at room temperature, as shown in Scheme 53. Two differently N-substituted imines were investigated under these conditions.…”
Section: Magnesium-catalyzed 12-nucleophilic Additions To Carbonyl Cmentioning
confidence: 99%
“…For example, Antilla et al have reported a novel methodology to add diphenylphosphine oxide 166a to imines with generally moderate to quantitative yields (65-98%) and enantioselectivities of up to 99% ee. 90 The process was catalyzed with only 5 mol% of chiral phosphate magnesium complex 190 in acetonitrile at room temperature, as shown in Scheme 53. Two differently N-substituted imines were investigated under these conditions.…”
Section: Magnesium-catalyzed 12-nucleophilic Additions To Carbonyl Cmentioning
confidence: 99%
“…177,[182][183][184] The biological importance of this class of compounds continues to drive efforts toward their efficient and rapid synthesis. [185][186][187][188][189][190][191][192][193][194] or an amide, 195 whereas, the Kabachnik-Fields reaction is a three-component reaction of an amine, an aldehyde, and a dialkyl phosphite. [196][197][198] Alternatively, α-amino phosphonic acids can be prepared through C−C bond formation, either through the addition of an anionic phosphonic analogue of glycine to an electrophilic carbon atom (Scheme 30, pathway c) or through the addition of a nucleophile to a cationic phosphoglycine equivalent (Scheme 30, pathway d).…”
Section: Significance Of α-Amino Phosphonic Acids and Derivativesmentioning
confidence: 99%
“…Antilla et al also investigated chiral calcium BINOL phosphate catalysts [94]; for reviews of asymmetric phospination reactions, see [95,96]. This type of calcium catalyst was applied to asymmetric phosphination reactions (Table 24).…”
Section: Asymmetric Mannich and Related Reactionsmentioning
confidence: 99%